2017
DOI: 10.1039/c7cs00485k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reduction of large sized graphene oxide sheets

Abstract: Graphene oxide (GO) can be considered as one of the most visible outcomes of graphene research in terms of large scale production and commercialization prospects. Although GO can be easily prepared by oxidation-exfoliation of graphite in agitated solutions, the size of these sheets is generally limited due to fragmentation along fault lines during chemical oxidation and exfoliation in agitated solutions. In this account, we discuss recent strategies which have been developed for the preparation of large sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
142
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(145 citation statements)
references
References 96 publications
1
142
0
2
Order By: Relevance
“…GO aqueous dispersions have adjustable rheology, which enable them to work as high‐performance ink for various fabrication techniques . In addition, the large lateral sized GO sheets are beneficial to achieve higher shear viscosity and storage modulus than the smaller GO sheets in aqueous solution, which help obtain printable ink at a relatively low solid content and thus favor printing of low‐density graphene structures. We experimentally found that the aqueous‐based ink with a solid content of 2.5 wt% is very promising for 3D printing (Figure S2c,d, Supporting Information).…”
mentioning
confidence: 99%
“…GO aqueous dispersions have adjustable rheology, which enable them to work as high‐performance ink for various fabrication techniques . In addition, the large lateral sized GO sheets are beneficial to achieve higher shear viscosity and storage modulus than the smaller GO sheets in aqueous solution, which help obtain printable ink at a relatively low solid content and thus favor printing of low‐density graphene structures. We experimentally found that the aqueous‐based ink with a solid content of 2.5 wt% is very promising for 3D printing (Figure S2c,d, Supporting Information).…”
mentioning
confidence: 99%
“…16,17 We produced continuous GO films having a thickness of ~ 5.5 nm on UVO-treated glass (Figure S2(a)). RGO was produced from GO substrates by classical low thermal reduction of GO substrates 18,19 (Explained in detailed in Supplementary Information). RGO substrates had a blackish appearance (compared to a slight brown tint of GO), consistent with reduction of oxide groups (Figure S1) and verified with XPS (Figure 1(a) and Table 1).…”
Section: Preparation and Characterization Of Gbm Substratesmentioning
confidence: 99%
“…20,21 Upon thermal reduction more than 50% of epoxy, carbonyl and carboxyl functional groups were removed; however, the hydroxyl functional groups were almost unchanged (Figure 1(b) and Table 1). Studies have shown that highly stable hydroxyls and carbonyl groups are difficult to remove from the graphene sheet edges at low temperature reduction without inducing detects; 18,19 as a result, RGO retains 15 -25 % residual oxygen concentration upon low thermal reduction.…”
Section: Preparation and Characterization Of Gbm Substratesmentioning
confidence: 99%
“…Graphene flakes exfoliated by high power sonication of graphite are also provided as dispersion for solution processing. Graphene thin films (not single layer) are also obtained from previously deposited GO films by chemical reduction with different techniques (delivering the so‐called reduced graphene oxide, rGO), but with poor quality compared with that of CVD monolayer graphene . The inverse procedure, namely, electrochemical oxidation of graphene by local anodic oxidation (LAO) appears as a suggestive patterning technique to achieve a direct integration of single layers of both materials with the highest quality, optimal control, and precision.…”
Section: Introductionmentioning
confidence: 99%